1974
DOI: 10.1143/jjap.13.189
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Ultrasound to Nematic Liquid Crystal

Abstract: Corrosion-related defects in pure Al and AA 2037 Al alloy have been investigated by positron beam-based Doppler broadening energy spectroscopy. Defect profiles have been analyzed by measuring the S parameter as a function of incident positron energy up to 30 keV. When pure Al samples are immersed in 1M NaOH for various times, a significant increase in the S parameter near the surface is observed. This implies that the corrosion process involves the creation of defects and nanometer voids. In contrast, a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…But along with that broadening, the center of the peak is also shifted with respect to the ð2 2 0 4ÞÀpeak of sapphire. This represents an overall tilting of the epitaxial layer with respect to sapphire substrate, and is similar to the Nagai-like tilt observed in other material systems [13]. Since such a shift does not appear for Q x J½1 1 0 0 conditions, this allows us to conclude that the tilting of the ð1 1 2 0ÞÀplanes occur along the c-direction as shown schematically in Fig.…”
Section: Resultssupporting
confidence: 84%
“…But along with that broadening, the center of the peak is also shifted with respect to the ð2 2 0 4ÞÀpeak of sapphire. This represents an overall tilting of the epitaxial layer with respect to sapphire substrate, and is similar to the Nagai-like tilt observed in other material systems [13]. Since such a shift does not appear for Q x J½1 1 0 0 conditions, this allows us to conclude that the tilting of the ð1 1 2 0ÞÀplanes occur along the c-direction as shown schematically in Fig.…”
Section: Resultssupporting
confidence: 84%
“…This arises because of the in-plane anisotropy in the lattice-mismatch and the miscut of the substrate. Such a shift is basically a signature of ''Nagai-tilt'' [13] in the layer, details of which are discussed in a separate work [14]. In the RSM, along with the InN-peak there is an additional peak which appears for all the InN samples grown on GaN buffer layers.…”
Section: Resultsmentioning
confidence: 93%
“…In our case, TEM diffraction analysis showed the MDs to be of the 60 type. It was shown by Nagai (1974) that, when the substrate surface was inclined with respect to (001) plane, such a network made the layer planes slope from the substrate ones. We found that the tilt rose upwards.…”
Section: Discussionmentioning
confidence: 99%